2020
DOI: 10.21203/rs.3.rs-34579/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nrf2 protects against seawater drowning-induced acute lung injury via inhibiting ferroptosis

Abstract: Background: Ferroptosis is a new type of nonapoptotic cell death model that was closely related to ROS accumulation. Seawater drowning-induced acute lung injury (ALI) which is caused by severe oxidative stress injury, has been a major cause of accidental death worldwide. The latest evidences indicate nuclear factor (erythroid-derived 2)-like 2 (Nrf2) suppress ferroptosis and maintain cellular redox balance. Here, we test the hypothesis that activation of Nrf2 pathway attenuates seawater drowning-induced ALI vi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 39 publications
(56 reference statements)
2
11
0
Order By: Relevance
“…It is reported that ML385 could directly bind to the NEH1 region of Nrf2 and consequently prevent the binding of Nrf2 and ARE sequence, thus inhibiting the activation of Nrf2/ARE pathway 52 . ML385 has been widely used in former studies to investigate the protective effects of Nrf2/ARE pathway 53,54 . In our study, we found that ML385 significantly inhibited the sustain of TJs and the decreased expression of MMPs.…”
Section: Discussionsupporting
confidence: 52%
“…It is reported that ML385 could directly bind to the NEH1 region of Nrf2 and consequently prevent the binding of Nrf2 and ARE sequence, thus inhibiting the activation of Nrf2/ARE pathway 52 . ML385 has been widely used in former studies to investigate the protective effects of Nrf2/ARE pathway 53,54 . In our study, we found that ML385 significantly inhibited the sustain of TJs and the decreased expression of MMPs.…”
Section: Discussionsupporting
confidence: 52%
“…Genetic or pharmacological suppression of Nrf2 expression could increase sorafenib’s anticancer activity in both vitro and tumor xenograft models [ 7 ]. While in other stress-induced diseases, ferroptosis inhibition resulting from Nrf2 activation helps protect against oxidative stress and maintain tissue homeostasis [ 27 , 30 , 31 ]. Consequently, targeting Nrf2-regulated ferroptosis as a therapeutic strategy should take specific pathological contexts into account.…”
Section: Several Canonical Ferroptosis Modulatorsmentioning
confidence: 99%
“…Nuclear factor (erythroid‐derived 2)‐like 2 (Nrf2) is a vital regulator in intracellular oxidation homeostasis as well as lipid peroxidation. Activation of Nrf2 inhibits ferroptosis against ALI, such as intestinal ischemia/reperfusion‐induced ALI, seawater drowning‐induced ALI, and LPS‐induced ALI 43–45 . ATF3 represses Nrf2‐mediated signaling by directly binding to Nrf2 protein, and meanwhile, ATF3 promoter contains the consensus antioxidant response element (ARE), the binding site for Nrf2 46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…Activation of Nrf2 inhibits ferroptosis against ALI, such as intestinal ischemia/reperfusion-induced ALI, seawater drowninginduced ALI, and LPS-induced ALI. [43][44][45] ATF3 represses Nrf2-mediated signaling by directly binding to Nrf2 protein, and meanwhile, ATF3 promoter contains the consensus antioxidant response element (ARE), the binding site for Nrf2. 46,47 Further study may focus on the crosstalk between ATF3 and Nrf2 to explore a new mechanism for the pro-ferroptotic effect of ATF3.…”
Section: Discussionmentioning
confidence: 99%